THE USE OF PRESUPPOSITION IN BUSINESS MODEL CANVAS OF START FRIDAY’S WEBSITE CONTENT - YOSARIA INDAH, RAFIKA (LANGUAGE HORIZON, 2017)
pengungkapan elemen-elemen di dalam Business Model Canvas menggunakan teori Osterwalder and Pigneur (2009) dan teori fungsi pragmatik (Ge, 2011) dengan menggunakan teori presaposisi (Yule, 1996) di kalimat-kalimat deskripsi dalam konten website Start Friday. Dalam hal ini, kalimat-kalimat deskripsi di website Start Friday adalah objek utamanya. Metode dari penelitian ini menggunakan analisis deskriptif kualitatif. Penelitian ini menemukan bahwa presaposisi existential yang paling banyak digunakan di dalam konten website Start Friday. Yang mana, presaposisi existential tersebut mempunyai fungsi pragmatik untuk meringkas, menekankan, serta menarik keberadaan layanan kepada para pembaca website atau pelanggan. Bagaimanapun, penelitian ini akan memberikan pengetahuan mengenai fungsi pragmatik dalam bentuk presaposisi di dalam konten website Start Friday yang dapat mengungkapkan elemen-elemen Business Model Canvas. Sebagaimana hal itu dapat disimpulkan bahwa presaposisi dan fungsi pragmatik dapat menjadi alat yang hebat untuk membuat perencanaan bisnis yang efektif dalam sebuah konteks bisnis bagi perusahaan dengan menggunakan bentuk Business Model Canvas. Hal tersebut juga menjadi strategi pemasaran untuk mengenalkan layanan-layanan yang ditawarkan dan kemampuan mereka pada para pembaca website maupun pelanggan mereka. Kata Kunci: periklanan, konten website, Business Model Canvas, website Start Friday, presaposisi.   Abstract This research focuses on the revealing the elements of Business Model Canvas (BMC) by Osterwalder and Pigneur (2009) and theory of pragmatics function (Ge; 2011) by using presupposition (Yule; 1996)  in description sentences of Start Friday’s website content. In this case, the description sentences in Start Friday’s website is the main object. The method of this study is using the descriptive qualitative analysis. This research found that the existential presupposition is generally used on the description sentences in website content of Start Friday. In which, the existential presupposition in those description sentences have the pragmatics function to concise, emphasize, and interest toward the service existence to the website readers’ or customers’ view. Furthermore, this research will give knowledge about pragmatics function in form of presupposition used in website content of Start Friday which can reveal the elements of Business Model Canvas (BMC). In which, it can be inferred that presupposition and pragmatics function can be the powerful tool to make the effective business plan in business context for the company by using the form of Business Model Canvas (BMC). It also becomes a marketing strategy for presenting the services offered and their capability to their website readers or customers. Keywords:  advertising, website content, Business Model Canvas, Start Friday website, presupposition.